EPCO-04. GENOMIC AND EPIGENOMIC HALLMARKS OF SCHWANNOMATOSIS SCHWANNOMAS. (9th November 2020) - Mansouri, Sheila; Suppiah, Suganth; Mamatjan, Yasin; Paganini, Irene; Liu, Jeff; Karimi, Shirin; Patil, Vikas; Nassiri, Farshad; Singh, Olivia; Sundaravadanam, Yogi; Rath, Prisni; Sestini, Robert; et al.
Abstract: Schwannomatosis (SWNTS) is a genetic cancer predisposition syndrome that manifests as multiple and often, painful neuronal tumors called schwannomas (SWNs). Very little is known about the epigenomic and genomic alterations in SWNTS related SWNs (SWNTS-SWNs) other than germline mutations in SMARCB1 and LZTR1 plus somatic mutations in NF2 and loss of heterozygosity in chromosome 22q. Herein, we have comprehensively established the specific molecular signatures of SWNTS-SWNs. We found that tumor anatomic location was associated with pain and distinct DNA methylation and transcriptional signatures. DNA sequencing revealed several novel non-22q deletions, specifically in LZTR1 -mutant cases. Whole-genome sequencing identified novel recurrent structural rearrangements. Further, chromosomal aberrations in SWNTS-SWNs were accompanied by increased transcription of mismatch repair genes. Our transcriptome analysis detected the SH3PXD2A-HTRA1 gene fusion in SWNTS-SWNs, more commonly in LZTR1 -mutant tumors. In addition, we identified the specific genetic, epigenetic, and transcriptional hallmarks of painful SWNs that may be harnessed to develop new treatments for this debilitating syndrome.